ASPEK – ASPEK INDIVIDUAL TERHADAP PERTIMBANGAN PROFESIONAL AUDITOR - Wiwi Idawati (BAJ: Behavioral Accounting Journal, 2021)
This research is a quantitative study that aims to find out the influence of auditor experience and gender on the auditor's professional considerations. This study used auditors working at the Public Accounting Firm in the DKI Jakarta area as samples. Sampling using random sampling methods with a sample number of 101 auditors worked at 30 Public Accounting Firms in the DKI Jakarta area. Hypothesis testing in this study used multiple linear regression analysis using the SPSS version 23 program with a significance level of 0.05%. The results of the test showed that (1) there was a significant influence on the auditor's work experience on the auditor's professional considerations, (2) there was no gender influence on the auditor's professional considerations